Needs Analysis of Development FBO Media as a Support for Blended learning in Al-Qur’an Hadits Lesson - Miftah Hur Rahman Zh; Nindya Liftia Sani; Dedi Kuswandi; Muhibuddin Fadhli (UIR Press, 2024)
The rapid development of science and technology has a significant impact on learning practices in formal educational institutions such as MAN. On the other hand, the implementation of the Merdeka Curriculum requires students to learn independently and requires the development of learning media that can be accessed in face-to-face and online learning. This study aims to analyze the needs of students and teachers at MAN Kota Batu for the development of FBO Media to support blended learning in Al-quran Hadith Lessons. The research was conducted at Madrasah Aliyah Negeri Kota Batu using a the ADDIE type (Analyze, design, development, implementation, and evaluation) with qualitative approach. The research subjects were the teachers and students of Al-Qur'an Hadith class X MAN Kota Batu. The results showed that in general: (1) there are problems in using the Al-Qur'an Hadith textbooks as the main source, (2) students need flexible learning materials and media, (3) the infrastructure owned by MAN Kota Batu is sufficient to implement blended learning with FBO Media, (4) using FBO media can be an alternative as a flexible media to support blended learning. Based on this results, it is recommended that future researchers explore the development process of online flipbook media and evaluate its effectiveness on student learning outcomes in blended learning environments.